2022
DOI: 10.3837/tiis.2022.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Rule-based Healthcare Edits

Abstract: Automated medical claims processing and billing is a popular application domain of information technology. Managing medical related data is a tedious job for healthcare professionals, which distracts them from their main job of healthcare. The technology used in data management has a sound impact on the quality of healthcare data. Most of Information Technology (IT) organizations use conventional software development technology for the implementation of healthcare systems. The objective of this experimental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Medical diagnosis applications often use AI-RBSs with medical image processing to select surgical strategies and for other medical tasks [50][51][52][53][54][55]. In reviewing applications of AI-RBS in health systems, both Matsuyama [56] and Abdullah et al [57] have concluded that this way of organizing knowledge can increase the flexibility of software systems and that it is more efficient than conventional approaches, in some cases increasing the confidence in the value of the results to 95%. al Fryan et al [54] recommend using these technologies in other fields of study due to the efficiency of the processes.…”
Section: Introductionmentioning
confidence: 99%
“…Medical diagnosis applications often use AI-RBSs with medical image processing to select surgical strategies and for other medical tasks [50][51][52][53][54][55]. In reviewing applications of AI-RBS in health systems, both Matsuyama [56] and Abdullah et al [57] have concluded that this way of organizing knowledge can increase the flexibility of software systems and that it is more efficient than conventional approaches, in some cases increasing the confidence in the value of the results to 95%. al Fryan et al [54] recommend using these technologies in other fields of study due to the efficiency of the processes.…”
Section: Introductionmentioning
confidence: 99%